International Travel Survey, 2005 - Statistics Canada (Abacus Data Network, 2005)
Records relate to the activities of Canadians travelling outside the country and visitors to Canada; port of entry; Canadian residents; persons; non-residents; vehicles; receipts; payments; country of residence;expenditures; length of stay; type of transportation; purpose of trip; accommodation used; expenditure by categories; age groups. International travel data is collected in four flows: Canadians returning from the USA; Canadians returning from other countries; visitors from the USA to Canada; visitors from other countries to Canada. Note: corrections were made to the revised edition of Overseas Resident, Trips to Canada for the all quarters of 2005 and the United-States Resident, Trips to Canada for quarters 2 and 3 of 2005. In the case of the overseas visitor master data files, we corrected the number of nights spent in Newfoundland from 2 to 20 on one record. Also, for 67 records where visitors indicated that they came directly to Canada, we modified their answers to "number of nights spent in the United States before entering Canada" to "not applicable". In the case of the U.S. visitor master data files, we corrected the spending by category for 3 records.